Indicators for technology generation effectiveness in dairying in Ethiopia - Wodajo, Workneh Abebe (Indian Journal of Dairy Science, 2017)
Dairy research is being undertaken since 1960s in Ethiopia. However, the majority of the farmers still continue to use traditional practices. This study was carried out to look into the effectiveness of research in generating improved dairy practices. To achieve the objective of the study, cross sectional survey was employed using 50 researchers in the area of livestock sector. A systematic sampling technique was employed to identify the sample respondents. Holistically, to capture all the relevant information, mixed methods such as focus group discussion, key informant interview, questionnaire and observation were used for data collection. The data were analyzed developing dairy research effectiveness index, ordered logit regression analysis and content analysis. The study brought out that the dairy research effectiveness index developed using the score of sub indicators such as personal characteristics, research participation, research infrastructure, research management, responsiveness of improved dairy practices, research policy, social participation and financial capacity indicated the low level of the dairy research effectiveness. The ordered logit regression analysis also indicated that research participation and responsiveness of improved dairy practices were significantly influencing the effectiveness of dairy research. Â Thus, developing culture of collaboration program with experienced countries in dairy research is a pragmatic approach whereby dairy researchers can be capacitated through experience sharing and staff exchange program for improving the dairy research. Likewise, strengthening financial capacity of researchers, fulfilling research infrastructure, developing research policy and improving research managerial skills are the main areas that need the attention of top research executives.Â